The crime of aggression under the Rome Statute of the International Criminal Court / Carrie McDougall, The University of Melbourne. - McDougall, Carrie, 1978- (Cambridge studies in international and comparative law ;, 2021)
After the crime of aggression was adopted under the Rome Statute of the International Criminal Court, Carrie McDougall used her intimate involvement in the crime's negotiations, combined with extensive scholarly reflection to produce the first and most comprehensive academic study. This updated second edition offers an exhaustive and sophisticated legal analysis of the crime's definition, as well as the provisions governing the ICC's exercise of jurisdiction over the crime. It explores the desirability of holding individuals to account for unlawful uses of inter-State armed force, the geo-political significance of the crime and a range of practical issues likely to arise in prosecutions before both the ICC and domestic courts. This book is highly relevant to all academics and practitioners interested in the crime of aggression, as well as broader issues relating to the prohibition of the use of force, international criminal law and the ICC.